Temporal lobe epilepsy in cats. (January 2023) - Pakozdy, Akos; Halasz, Peter; Klang, Andrea; Lörincz, Borbala A.; Schmidt, Martin J.; Glantschnigg-Eisl, Ursula; Binks, Sophie
Abstract: In recent years there has been increased attention to the proposed entity of feline temporal lobe epilepsy (TLE). Epileptic discharges in certain parts of the temporal lobe elicit very similar semiology, which justifies grouping these epilepsies under one name. Furthermore, feline TLE patients tend to have histopathological changes within the temporal lobe, usually in the hippocampus. The initial aetiology is likely to be different but may result in hippocampal necrosis and later hippocampal sclerosis. The aim of this article was not only to summarise the clinical features and the possible aetiology, but also being work to place TLE within the veterinary epilepsy classification. Epilepsies in cats, similar to dogs, are classified based on the aetiology into idiopathic epilepsy, structural epilepsy and unknown cause. TLE seems to be outside of this classification, as it is not an aetiologic category, but a syndrome, associated with a topographic affiliation to a certain anatomical brain structure. Magnetic resonance imaging, histopathologic aspects and current medical therapeutic considerations will be summarised, and emerging surgical options are discussed. Highlights: Feline temporal lobe epilepsy (fTLE) is a syndrome with characteristic ictal signs. These include orofacial automatisms with lip smacking, facial twitching and chewing. fTLE is not an aetiologic category of epilepsy, as several aetiologies may cause fTLE. If present, brain MRI changes are usually within the hippocampus. Drug management includes phenobarbital and levetiracetam.